2019
DOI: 10.1016/j.ejc.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Rooted forests that avoid sets of permutations

Abstract: We say that an unordered rooted labeled forest avoids the pattern π ∈ Sn if the sequence obtained from the labels along the path from the root to any vertex does not contain a subsequence that is in the same relative order as π. We enumerate several classes of forests that avoid certain sets of permutations, including the set of unimodal forests, via bijections with set partitions with certain properties. We also define and investigate an analog of Wilf-equivalence for forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 19 publications
(39 reference statements)
1
28
0
Order By: Relevance
“…In other words, labels on any path from a root to a vertex for a forest in F n (21) form an increasing sequence. Let F n (τ (1) , . .…”
Section: Hypercubic Ideals and Restricted Parking Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, labels on any path from a root to a vertex for a forest in F n (21) form an increasing sequence. Let F n (τ (1) , . .…”
Section: Hypercubic Ideals and Restricted Parking Functionsmentioning
confidence: 99%
“…, τ (s) } of patterns. The enumeration of rooted-labelled forests on [n] that avoid various patterns are obtained in [1]. In particular, it is shown that [11,12]).…”
Section: Hypercubic Ideals and Restricted Parking Functionsmentioning
confidence: 99%
See 3 more Smart Citations